2010
DOI: 10.3109/09638288.2010.503256
|View full text |Cite
|
Sign up to set email alerts
|

Measuring substantial reductions in functioning in patients with chronic fatigue syndrome

Abstract: Purpose All of the major current case definitions for chronic fatigue syndrome (CFS) specify substantial reductions in previous levels of occupational, educational, social, or personal activities to meet criteria. Difficulties have been encountered in operationalizing “substantial reductions.” For example, the Medical Outcomes Study Short Form-36 Health Survey (SF-36) has been used to determine whether individuals met the CFS disability criterion. However, previous methods of using the SF-36 have been prone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
75
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 30 publications
5
75
1
1
Order By: Relevance
“…Jason, Evans, et al (2011) found that the MFI did identify all CFS cases, but these scales were not able to successfully identify those who did not have CFS. In addition, Jason, Brown, et al (2011) examined Reeves et al’s recommended use of selected subscales from the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) to measure disability. Notably, Jason, Brown, et al (2011) found that the Reeves et al recommended cutoff of less than or equal to 66.7 on the SF-36 Role-Emotional subscale would select the majority of those with chronic fatigue explained by psychiatric reasons as meeting the CFS disability criterion.…”
Section: Case Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jason, Evans, et al (2011) found that the MFI did identify all CFS cases, but these scales were not able to successfully identify those who did not have CFS. In addition, Jason, Brown, et al (2011) examined Reeves et al’s recommended use of selected subscales from the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) to measure disability. Notably, Jason, Brown, et al (2011) found that the Reeves et al recommended cutoff of less than or equal to 66.7 on the SF-36 Role-Emotional subscale would select the majority of those with chronic fatigue explained by psychiatric reasons as meeting the CFS disability criterion.…”
Section: Case Definitionsmentioning
confidence: 99%
“…In addition, Jason, Brown, et al (2011) examined Reeves et al’s recommended use of selected subscales from the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36) to measure disability. Notably, Jason, Brown, et al (2011) found that the Reeves et al recommended cutoff of less than or equal to 66.7 on the SF-36 Role-Emotional subscale would select the majority of those with chronic fatigue explained by psychiatric reasons as meeting the CFS disability criterion. Furthermore, the area under the curve (AUC) for the Role-Emotional subscale was the worst among the eight SF-36 subscales for discriminating patients with CFS from controls (Jason, Brown, et al, 2011).…”
Section: Case Definitionsmentioning
confidence: 99%
“…In fact, Jason et al (2009) found that 38% of individuals who had primarily a Major Depressive Disorder (MDD) were misclassified as having CFS using the Reeves empiric CFS case definition (2005). In further support of this critique by Jason et al (2009), Jason et al (2011) found that the Role Emotional subscale had the worst sensitivity and specificity of all the SF-36 subscales using responses from both a community-based sample and a tertiary care sample.…”
mentioning
confidence: 91%
“…Ware et al (2000) found that the mean for Role-Emotional for a clinical depression group was 38.9, indicating that almost all those with clinical depression would meet the CFS disability criterion, as they would be within the lower 25th percentile on this subscale. Jason et al (2010c) found that Role-Emotional had the lowest threshold for both identifying individuals with CFS and identifying others who did not have this illness. However, Vitality, Social Functioning and Role-Physical have the highest threshold.…”
Section: Substantial Reduction In Functioningmentioning
confidence: 99%
“…However, Vitality, Social Functioning and Role-Physical have the highest threshold. In a literature review, the Vitality, Social Functioning and RolePhysical subscales best discriminated those with CFS from controls (Jason et al, 2010c). The Vitality scale measures items that assess feeling full of pep and energy, as well as those that focus on feeling worn out or tired.…”
Section: Substantial Reduction In Functioningmentioning
confidence: 99%